In vivo transplantation of 3D encapsulated ovarian constructs in rats corrects abnormalities of ovarian failure. Issue 1 (December 2017) - Sittadjody, Sivanandane; Saul, Justin; McQuilling, John; Joo, Sunyoung; Register, Thomas; Yoo, James; Atala, Anthony; Opara, Emmanuel
Abstract Safe clinical hormone replacement (HR) will likely become increasingly important in the growing populations of aged women and cancer patients undergoing treatments that ablate the ovaries. Cell-based HRT (cHRT) is an alternative approach that may allow certain physiological outcomes to be achieved with lower circulating hormone levels than pharmacological means due to participation of cells in the hypothalamus-pituitary-ovary feedback control loop. Here we describe the in vivo performance of 3D bioengineered ovarian constructs that recapitulate native cell–cell interactions between ovarian granulosa and theca cells as an approach to cHRT. The constructs are fabricated using either Ca++ or Sr++ to crosslink alginate. Following implantation in ovariectomized (ovx) rats, the Sr++ -cross-linked constructs achieve stable secretion of hormones during 90 days of study. Further, we show these constructs with isogeneic cells to be effective in ameliorating adverse effects of hormone deficiency, including bone health, uterine health, and body composition in this rat model. Cell-based hormone replacement therapy (cHRT) may be an alternative therapy to pharmacological (p)HRT. Here, the authors show that implanted 3D bioengineered ovarian constructs of granulosa and theca cells in ovariectomized rats recapitulate native cell interactions and improve efficacy compared to similar doses of pHRT.